2018
DOI: 10.5603/fm.a2017.0063
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of garlic extract against maternal and foetal cerebellar damage induced by lead administration during pregnancy in rats

Abstract: This study was useful in evaluating the hazardous effects of uncontrolled use of Pb in general and in assessing the developmental and neurotoxicity of foetuses due to exposure during pregnancy in particular. Co-administration of garlic has beneficial effects in amelioration of Pb-induced neurotoxicity and reversing the histopathological changes of the cerebellum of mother rats and foetuses. (Folia Morphol 2018; 77, 1: 1-15).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
7
4
0
Order By: Relevance
“…Additionally, degenerating pyknotic cells and vacuolation in the Purkinje cell layer were easily detected in the Pb group. Similarly, previous studies reported that Pb exposure during cerebellar development significantly decreased the number of Purkinje cells and ascorbic acid treatment mitigated Pb-induced impairments in the PA group [17,20,34,35,36]. Our results are consistently similar with previous studies, which observed that ascorbic acid prevents the harmful effects of other heavy metals including mercury and cadmium on brain development [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, degenerating pyknotic cells and vacuolation in the Purkinje cell layer were easily detected in the Pb group. Similarly, previous studies reported that Pb exposure during cerebellar development significantly decreased the number of Purkinje cells and ascorbic acid treatment mitigated Pb-induced impairments in the PA group [17,20,34,35,36]. Our results are consistently similar with previous studies, which observed that ascorbic acid prevents the harmful effects of other heavy metals including mercury and cadmium on brain development [37,38].…”
Section: Discussionsupporting
confidence: 92%
“…The findings suggested that garlic may protect against lead-induced neuronal cell apoptosis in the developing hippocampus of rat pups [ 45 ]. The beneficial effects of this natural antioxidant in protecting against lead toxicity were also noted in other studies [ 46 , 47 ]. Co-administration of lead (at a dose of 160 and 320 mg/kg bw) with garlic extract (250 mg/kg bw) to pregnant rats resulted in reductions in lead levels not only in the mother’s blood but also in the cerebellum, placenta, and fetal brain [ 47 ].…”
Section: Herbal Medicines Used To Counteract Infections During Pregnancysupporting
confidence: 75%
“…The beneficial effects of this natural antioxidant in protecting against lead toxicity were also noted in other studies [ 46 , 47 ]. Co-administration of lead (at a dose of 160 and 320 mg/kg bw) with garlic extract (250 mg/kg bw) to pregnant rats resulted in reductions in lead levels not only in the mother’s blood but also in the cerebellum, placenta, and fetal brain [ 47 ]. In immunohistochemical staining, a reduction in the number of Purkinje cells in the cerebellum was observed in the group of animals exposed to lead.…”
Section: Herbal Medicines Used To Counteract Infections During Pregnancysupporting
confidence: 75%
“…Previous studies con rmed that CP can penetrate the placental barrier and induce congenital malformation in fetuses [31]. On the other hand, placental transfer of garlic components was recorded by Saleh et al [32].…”
Section: Introductionmentioning
confidence: 95%